Analysis of virgin coconut oil and its potential in food, nutrition, and health - Maruli Tua Sinaga, Alexander; Permadi, Adi; Sofiana, Nurani; Firdaus, Stradivary Maulida; Putri, Mutiara Wilson; Nazzal, Sami; Mohamed, Farahidah (Universitas Ahmad Dahlan, Indonesia, 2025)
Virgin coconut oil (VCO), renowned for its exceptional nutritional and therapeutic properties, has garnered significant interest as a functional food and health supplement. Coconut trees (Cocos nucifera L.) play a vital role in the livelihoods of millions of farmers in Indonesia and are a source of highly valuable products, including VCO. This study analyzes VCO’s composition, quality, and safety to optimize its food, nutrition, and health applications. The research involved processing coconut kernels into oil and conducting a series of tests at an accredited laboratory, including peroxide value analysis, fatty acid profiling, and microbiological assessments. The results demonstrate that the VCO produced in this study has a peroxide value of 0.08 mEq O2/kg and a moisture content of 0%, indicating high stability and excellent quality. Fatty acid analysis revealed a high content of saturated fatty acids (92.505%), particularly lauric acid, known for its antimicrobial and anti-inflammatory properties. Microbiological tests confirmed the absence of pathogenic microorganisms such as Escherichia coli and Salmonella sp., as well as heavy metals like lead (Pb), mercury (Hg), and cadmium (Cd), ensuring safety for consumption. In conclusion, the findings highlight VCO’s superior quality, stability, and safety, underscoring its potential as a functional food ingredient and health supplement. Further research is recommended to explore its applications in nutraceutical formulations and advanced studies on its bioactive compounds.